ASPECTS OF THE EUROPEAN SYSTEM OF FINANCIAL SUPERVISION - Nagy, Zoltán B; Csiszár, Anett S (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
The study presents the main stages of the development of the European financial supervisory regulation and the current European System of Financial Supervision. The financial economic crisis highlighted the weaknesses in the supervisory system and the fact that the supervisor has an important role in consumer protection and in the mitigation of risk-taking by financial institutions. The European Union has developed a new financial strategy known as Banking Union, which has a three-pillar framework. These three pillars are the Single Supervisory Mechanism, the Single Resolution Mechanism and the Common Deposit Guarantee Scheme. This system is intended to achieve a single economic and monetary union at supranational level and to avoid the emergence of a new crisis as far as possible.